MUC16 and TP53 family co-regulate tumor-stromal heterogeneity in pancreatic adenocarcinoma - Chirravuri-Venkata, Ramakanth; Dam, Vi; Nimmakayala, Rama Krishna; Alsafwani, Zahraa Wajih; Bhyravbhatla, Namita; Lakshmanan, Imayavaramban; Ponnusamy, Moorthy P.; Kumar, Sushil; Jain, Maneesh; Ghersi, Dario; Batra, Surinder K. (Frontiers in Oncology, 2023)
MUC16/CA125 is one of the few oldest cancer biomarkers still used in current clinical practice. As mesothelium is an abundant source of MUC16 and a major contributor to stromal heterogeneity in PDAC, we investigated the regulation of MUC16 in tumor and stromal compartments individually. The trajectories constructed using the single-cell transcriptomes of stromal cells from KPC tumors demonstrated continuity in the trajectory path between MUC16-expressing mesothelial cells and other CAF subsets. Further, the tumor tissues of MUC16 whole-body knockout (KPCM) showed dysregulation in the markers of actomyosin assembly and fibroblast differentiation (iCAF and myCAF), indicating that MUC16 has an extra-tumoral role in controlling CAF differentiation. Although we found mesothelium-derivative stromal cells to be bystanders in normal pancreas, the proportion of these cells was higher in invasive PDAC, particularly in TP53 deficient tumors. Moreover, we also detail the regulation of MUC16, KRAS, and SOX9 by TP53 family members (TP53 and TP63) using multi-omics data from knockout models, PDAC cell lines, and human PDAC tissues.